1995
DOI: 10.1128/jb.177.22.6381-6389.1995
|View full text |Cite
|
Sign up to set email alerts
|

The three genes lipB, lipC, and lipD involved in the extracellular secretion of the Serratia marcescens lipase which lacks an N-terminal signal peptide

Abstract: The extracellular lipase of Serratia marcescens Sr41, lacking a typical N-terminal signal sequence, is secreted via a signal peptide-independent pathway. The 20-kb SacI DNA fragment which allowed the extracellular lipase secretion was cloned from S. marcescens by selection of a phenotype conferring the extracellular lipase activity on the Escherichia coli cells. The subcloned 6.5-kb EcoRV fragment was revealed to contain three open reading frames which are composed of 588, 443, and 437 amino acid residues cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 49 publications
(45 reference statements)
1
75
0
1
Order By: Relevance
“…4b) presented one band with lipolytic activity, which had an approximate mass of 58 kDa, presumably corresponding to the 62 kDa lipase LipA from S. marcescens (Akatsuka et al, 1995). The quantitative enzymic assay for lipolytic activity (Fig.…”
Section: Investigation Of Ahl-regulated Exoenzymes and Exoproteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b) presented one band with lipolytic activity, which had an approximate mass of 58 kDa, presumably corresponding to the 62 kDa lipase LipA from S. marcescens (Akatsuka et al, 1995). The quantitative enzymic assay for lipolytic activity (Fig.…”
Section: Investigation Of Ahl-regulated Exoenzymes and Exoproteinsmentioning
confidence: 99%
“…The structural organization and sequence conservation of the genes encoding the ABC protein translocation systems is highly conserved among the Gram-negative bacteria . The lipB operon of S. marcescens consists of three genes, lipBCD, encoding an inner-membrane ATPase (the ABC protein), a membrane fusion protein and an outer-membrane polypeptide, respectively (Akatsuka et al, 1995(Akatsuka et al, , 1997. S. liquefaciens MG1 has been demonstrated to be under the transcriptional control of N-butyryl-L-homoserine lactone (C4-HSL), which renders the production of extracellular protease activity indirectly under the control of quorum sensing .…”
mentioning
confidence: 99%
“…chrysanthemi prtDE genes (Letoff6 et al, 1990), we also found significant homology to the secretion guard for the Serratia marcescens lipase lipBC genes (Akatsuka et al, 1995) and metalloprotease hasDE genes (Letoff6 et al, 1993).…”
Section: Discussionmentioning
confidence: 79%
“…Although the genes involved in the synthesis and secretion of the extracellular proteins are usually clustered, the lipase and metalloprotease genes are not linked to lipBCD in S. marcescens but are linked to genes encoding products homologous to GDP-mannose pyrophosphorylase, an enzyme involved in the biosynthesis of lipopolysaccharide in Salmonella typhimurium and E. coli (Akatsuka et al, 1995). The structure of LPS plays an important role in the localization of secretory components such as TolC, PrtF and even PrtE in the outer membrane (Wandersman & Letoffk, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In each case the protease is secreted via an ABC transporter, often linked to the protease structural gene in the same operon. However, the genetic organization of the protease (prt) operon varies, as does the number of proteases secreted (Ahn et al, 1999;Akatsuka et al, 1995Akatsuka et al, , 1997Duong et al, 1992;Ghigo & Wandersman, 1992a, b;Guzzo et al, 1991b;Kawai et al, 1999).…”
Section: Introductionmentioning
confidence: 99%